Postoperative Pain After Robot-Assisted Laparoscopic Ventral Hernia Repair - Lindström, Per; Rietz, Göran; Everhov, Åsa Hallqvist; Sandblom, Gabriel (Frontiers in Surgery, 2021)
Background Robot-assisted ventral hernia repairmay reduce the risk for pain and discomfort in the postoperative period thus enabling shorter hospital stay. The aim of the present study was to evaluate postoperative pain following robot-assisted laparoscopic repair. The approach was selected after an intraoperative decision to complete the repair as: 1. Transabdominal Preperitoneal Repair (TAPP); 2. Trans-Abdominal RetroMuscular (TARM) repair; or 3. Intraperitoneal Onlay Mesh (IPOM) repair depending on anatomical conditions. Methods Twenty ventral hernia repairs, 8 primary and 12 incisional, were included between 18th Dec 2017 and 11th Nov 2019. There were 8 women, mean age was 60.3 years, and mean diameter of the defect was 3.8 cm. The repairs were performed at Södersjukhuset (Southern General Hospital, Stockholm) using the Da Vinci Si Surgical System® . Sixteen repairs were completed with the TAPP technique, 2 with the TARM technique, and 2 as IPOM repair. Results Mean hospital stay was 1.05 days. No postoperative infection was seen, and no recurrence was seen at 1 year. At the 30-day follow-up, fifteen patients (75%) rated their pain as zero or pain that was easily ignored, according to the Ventral Hernia Pain Questionnaire. After 1 year no one had pain that was not easily ignored. Conclusion The present study shows that robot-assisted laparoscopic ventral hernia is feasible and safe. More randomised controlled trials are needed to show that the potential benefits in terms of shorter operation times, earlier discharge, and less postoperative pain motivate the extra costs associated with the robot technique.